Bond men made free : medieval peasant movements and the English rising of 1381 - Hilton, R. H. (Rodney Howard), 1916-2002 (Routledge, 2003)
This account of the Peasant's Revolt of 1831 remains the classic authoratative text on the 'English Rising'.